The legal and social management of psychopaths - Mei-Tal, Maya (2005)
Psychopathy has been a cause for disquiet for many years and has received more attention in recent years. Questions regarding its validity as a mental disorder, its effects on moral agency and the management of individuals suffering from the disorder have been hard to answer. This thesis first seeks to define psychopathy and establish its status as a valid mental disorder. If psychopathy is a mental disorder, rather than a behavioural construct, it must give rise to certain questions of management. Various claims concerning the responsibility and moral agency of psychopaths are considered, concluding that the psychological formation of psychopathy negates moral agency. The thesis then asks whether the disorder of psychopathy predicts recidivism, both general and violent, and whether such prediction is геliable. Evaluation of the evidence suggests that psychopathy is a valid and reliable risk factor. Management is therefore considered essential, whether civil or criminal. Mental health management of psychopaths in England and Wales is examined, discussing both current law and proposed reforms. It is found that psychopathy is currently an untreatable disorder, making civil management contentious. Criminal justice management in England and Wales is then examined, notwithstanding the claim of psychopathic irresponsibility. It is recommended that psychopaths be confined indefinitely, for the protection of the public, in conditions superior to those offered in most institutions. It is advocated that research into the treatment of psychopathy continues with the hope of establishing successful programs